Stable isotopes and carbon and nitrogen ratio of hyperiid amphipod in the Southeast Pacific - Liliana Espinosa-Leal (PANGAEA, 2019)
Carbon and nitrogen value for hyperiid amphipods in the Southeast Pacific.